Improved 5-year survival of patients with immunochemical faecal blood test-screen-detected colorectal cancer versus non-screening cancers in northern Italy. Issue 1 (January 2015) - Parente, Fabrizio; Vailati, Cristian; Boemo, Cinzia; Bonoldi, Emanuela; Ardizzoia, Antonio; Ilardo, Antonina; Tortorella, Franco; Cereda, Danilo; Cremaschini, Marco; Moretti, Roberto
Abstract Background Colorectal cancer screening may reduce disease-related mortality by early-stage detection of cancers. Aims To study the effect of a single immunochemical faecal occult blood test (i-FOBt) screening round on reduction in colorectal cancer-related-mortality among average risk subjects. Methods Comparison of 5-year mortality rates in 3 cohorts from a Northern Italian province: (1) colorectal cancers detected at the 1st biennial round of a mass-screening programme targeting 50–69 years old subjects, (2) non-screening cancers symptomatically diagnosed during the same time period, and (3) cancers detected in the pre-screening biennium. Multivariate analyses were performed with the Cox regression model including tumour node metastasis (TNM) stage at diagnosis, anatomical distribution of cancers, age at diagnosis, gender and patient group. Kaplan–Meyer survival estimates and log-rank test for equality of survivor functions were calculated. Results Stage distribution significantly differed between screening and non-screening colorectal cancers: 73% of screen-detected colorectal cancers were stages I and II versus 43% and 40% of non-screening and pre-screening colorectal cancers. Cumulative 5-year mortality rate was significantly lower in screening compared to non-screening or pre-screening colorectal cancers patients (19% versus 37% and 41%, p < 0.001). Conclusions Colorectal cancers were detected at earlier stages in i-FOBT-positive subjects in comparison with non-screening patients; colorectal cancers found at screening had a significantly improved 5-year survival.